Etika, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai pada PT. Bank Rakyat Indonesia KC Jemursari Kota Surabaya - Niniet Tasya Violita; Oryza Tannar (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine ethics, work discipline and work environment on the performance of PT employees. Bank Rakyat Indonesia Jemursari Branch Office, Surabaya City. The research method used is quantitative research. By type and source of primary data. The results of this research are (1) ethics has no effect on the performance of PT employees. Bank Rakyat Indonesia KC Jemursari Surabaya City with a significance of 0.499 > 0.05, (2) work discipline influences the performance of PT employees. Bank Rakyat Indonesia KC Jemursari Surabaya City with a significance of 0.000 <0.05, (3) the work environment influences the performance of PT employees. Bank Rakyat Indonesia KC Jemursari, Surabaya City with a significance of 0.000 < 0.05. Conclusion, ethics has no effect on the performance of PT employees. Bank Rakyat Indonesia KC Jemursari Surabaya City, while work discipline and work environment influence the performance of PT employees. Bank Rakyat Indonesia KC Jemursari Surabaya City. Keywords: Work Discipline, Ethics, Employee Performance, Work Environment